Neoclassical Theory Versus Prospect Theory: Evidence from the Marketplace - List, John A. (Econometrica, 2004)
Several experimental studies have provided evidence that suggest indifference curves have a kink around the current endowment level. These results, which clearly contradict closely held economic doctrines, have led some influential commentators to call for an entirely new economic paradigm to displace conventional neoclassical theory--e.g., prospect theory, which invokes psychological effects. This paper pits neoclassical theory against prospect theory by investigating data drawn from more than 375 subjects actively participating in a well-functioning marketplace. The pattern of results suggests that prospect theory adequately organizes behavior among inexperienced consumers, but consumers with intense market experience behave largely in accordance with neoclassical predictions. Moreover, the data are consistent with the notion that consumers learn to overcome the endowment effect in situations beyond specific problems they have previously encountered. This "transference of behavior" across domains has important implications in both a positive and normative sense.